Analyst Coverage and Financing Decisions - CHANG, XIN; DASGUPTA, SUDIPTO; HILARY, GILLES (Journal of Finance, 2006)
ABSTRACT We provide evidence that analyst coverage affects security issuance. First, firms covered by fewer analysts are less likely to issue equity as opposed to debt. They issue equity less frequently, but when they do so, it is in larger amounts. Moreover, these firms depend more on favorable market conditions for their equity issuance decisions. Finally, debt ratios of less covered firms are more affected by Baker and Wurgler's (2002) “external finance‐weighted” average market‐to‐book ratio. These results are consistent with market timing behavior associated with information asymmetry, as well as behavior implied by dynamic adverse selection models of equity issuance.